2001
DOI: 10.1046/j.1439-0523.2001.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of AFLP markers for the identification of carrot breeding lines and F1 hybrids

Abstract: Four inbred lines of carrot (cytoplasmic male‐steriles and corresponding maintainers) and eight of their F1 hybrids were studied with the amplified fragment length polymorphism (AFLP) technique to examine their genetic relationship and produce markers useful for testing hybrid seed purity. Eighty‐six polymorphic amplicons were identified in bulked DNA samples using eight primer pair combinations. Genetic distance was estimated on the basis of the presence or absence of polymorphic bands. The dendrogram plotted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…0 0 1 1 CMS = cytoplasmic male sterility fore breeding stocks used for the production of F 1 hybrids usually retain a relatively high level of heterozygosity, which was demonstrated in earlier inveatigations (Grzebelus et al 2001) and confirmed in the present study. Interestingly, a higher level of variability, similar to that of the open-pollinated cv.…”
Section: Marker Namesupporting
confidence: 87%
See 3 more Smart Citations
“…0 0 1 1 CMS = cytoplasmic male sterility fore breeding stocks used for the production of F 1 hybrids usually retain a relatively high level of heterozygosity, which was demonstrated in earlier inveatigations (Grzebelus et al 2001) and confirmed in the present study. Interestingly, a higher level of variability, similar to that of the open-pollinated cv.…”
Section: Marker Namesupporting
confidence: 87%
“…The number of amplified products ranged from 9 (for the adaptor-specific primer carrying TCA as selective nucleotides) to 15 (ACT and GTA), and their length varied from 74 bp to 320 bp ( Table 2). The efficiency of DcMTD markers (9.3 polymorphic amplicons per primer combination) was only slightly lower than that obtained for AFLP markers (10.7 polymorphic amplicons per primer combination, Grzebelus et al 2001), and much higher than that obtained for RAPD markers (2.5 polymorphic amplicons per reaction, Grzebelus et al 1997) when similar plant materials were analysed.…”
Section: Variability Of Dcmaster Insertion Sitesmentioning
confidence: 54%
See 2 more Smart Citations
“…The usefulness of DNA polymorphism based on randomly amplified polymorphic DNA (Welsh and McClelland, 1990;Williams et al, 1990;Caetano-Anoles et al, 1991) has been proved in many species of vegetable crops such as tomato (Archak et al, 2002;Singh et al, 2007), cabbage (Cansian and Echeverrigaray, 2000), cucumber (Horejsi and Staub, 1996), eggplant (Karihaloo et al, 1995), melon (Garcia et al, 1998), pepper (Votava and Bosland, 2001;(Rodriguez et al, 1999), and carrot (Grzebelus et al, 1997). While there are some limitations of this type of DNA marker such as the dominant character, unreliability, strict dependence on the conditions of PCR reaction, they can, however, be very useful for genetic study of populations of vegetable plants, their wild relatives, breeding lines and hybrids.…”
Section: Introductionmentioning
confidence: 99%